Evaluation of cleaning efficiency of ultrafiltration membranes fouled by BSA using FTIR–ATR as a tool. (October 2015) - Luján-Facundo, M.J.; Mendoza-Roca, J.A.; Cuartas-Uribe, B.; Álvarez-Blanco, S.
Highlights: We studied the efficiency of two cleaning solutions to clean PES membranes. Cleaning efficiency was calculated for each membrane and cleaning agent tested. Quantification of residual proteins on the membrane was carried out by FTIR–ATR. P3-Ultrasil 115 was more efficient than NaOH solutions for membrane cleaning. FTIR–ATR is an excellent tool to help evaluating membrane fouling and cleaning. Abstract: The goal of this paper was to study the cleaning of two polyethersulfone (PES) membranes of different molecular weight and fouled with BSA solution. Ultrafiltration (UF) membranes were tested in a flat sheet module. Fouling experiments were carried out at a transmembrane pressure of 2 bar and cross flow velocity of 2 m/s during 2 h. Cleaning experiments were performed at 1 bar and 2.2 m/s. To compare the efficiency of different cleaning solutions (NaOH and P3-Ultrasil 115), quantification of residual proteins on the membrane was carried out by FTIR–ATR. To have a better understanding of the cleaning process, characteristics of the feed solution and of the membranes were considered and contact angle of the membranes before and after the cleaning was measured. Membrane resistances were also calculated at the different stages. Results from resistances showed that reversible fouling prevail over irreversible fouling for both membranes. P3-Ultrasil 115 was a better cleaning agent than NaOH solution since cleaning efficiencies (CE) of 100% for both membranes were achieved for P3-Ultrasil 115 solution. Residual proteins on the membrane after the cleaning were measured both by FTIR–ATR and Pierce-BCA method. Results showed that 100% of permeability recovery did not imply the complete BSA removal from the membrane. However, these measurements corroborated that P3-Ultrasil 115 had removed a higher amount of proteins than NaOH solution.